2021
DOI: 10.2196/29681
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality for Supporting the Treatment of Depression and Anxiety: Scoping Review

Abstract: Background Mental health conditions pose a major challenge to health care providers and society at large. The World Health Organization predicts that by 2030, mental health conditions will be the leading cause of disease burden worldwide. The current need for mental health care is overwhelming. In New Zealand, 1 in 6 adults has been diagnosed with common mental disorders, such as depression and anxiety disorders, according to a national survey. Cognitive behavioral therapy (CBT) has been shown to e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(53 citation statements)
references
References 50 publications
0
52
0
1
Order By: Relevance
“…It included two randomized controlled trials, two quasi-experimental studies without a control group and one quasi-experimental study with a control group, four of which showed positive results. More recently, a systematic review has included some randomized clinical trials with larger samples [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It included two randomized controlled trials, two quasi-experimental studies without a control group and one quasi-experimental study with a control group, four of which showed positive results. More recently, a systematic review has included some randomized clinical trials with larger samples [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It included two randomized controlled trials, two quasi-experimental studies without a control group and one quasi-experimental study with a control group, four of which showed positive results. More recently, a systematic review has included some randomized clinical trials with larger samples [43].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, depression among healthy older adults improved after playing Wii Fit (Nintendo) exergames twice per week for 4 weeks [ 59 ]; participants in the control group who participated in an education program for the same duration did not experience such improvements. A recent review also suggested that iVR therapies are effective in supporting the treatment of anxiety and depression [ 60 ].…”
Section: Discussionmentioning
confidence: 99%